ANALISIS PADA BUKU DONGENG KARAKTER UTAMA ANAK USIA DINI SETIA DAN JUJUR - Karyani, Runi; Respati, Resa; Sumardi, Sumardi (JURNAL PAUD AGAPEDIA, 2021)
This research is based on the importance of planting character values for early childhood. One that can instill character education for early childhood is through fairy tales. Fairy tales have many character values contained in them. Character education needs to be taught from an early age both formally and informally. The object of this research study is a fairy tale book entitled "Tales of the Main Character of Early Childhood Faithful and Honest" published by Bhuana Ilmu Popular in 2019. The purpose of this study is to describe in depth the values of loyal and honest early childhood character values by Heru Kurrniawan and Endah Kusumaningrum. There is a reason why the importance of character education is instilled from an early age through the fairy tale method, namely first, early childhood will be enthusiastic about listening to fairy tales. Second, the learning atmosphere will be fun. Third, with fairy tales with characters, children can know values Popular in 2019. The purpose of this study is to describe in depth the values of loyal and honest early childhood character values by Heru Kurrniawan and Endah Kusumaningrum. There is a reason why the importance of character education is instilled from an early age through the fairy tale method, namely first, early childhood will be enthusiastic about listening to fairy tales. Second, the learning atmosphere will be fun. Third, with fairy tales with characters, children can know valuesv character.Penelitian ini didasari karena pentingnya penanaman nilai-nilai karakter untuk anak usia dini. Salah satu yang dapat menanamkan pendidikan karakter untuk anak usia dini yaitu melalui dongeng. Dongeng memiliki banyak nilai-nilai karakter yang terkandung di dalamnya. Pendidikan karakter perlu diajarkan sejak dini baik secara formal maupun informal. Objek kajian penelitian ini yaitu buku dongeng yang berjudul â€œDongeng Karakter Utama Anak Usia Dini Setia dan Jujurâ€ yang diterbitkan oleh Bhuana Ilmu Populer pada tahun 2019. Tujuan penelitian ini yaitu untuk mendeskripsikan secara mendalam tentang nilai-nilai karakter anak usia dini setia dan jujur karya Heru Kurrniawan dan Endah Kusumaningrum. Terdapat alasan mengapa pentingnya pendidikan karakter ditanamkan sejak dini melalui metode dongeng, yakni pertama, anak usia dini akan antusias mendengarkan dongeng. Kedua, suasana belajar akan menyenangkan. Ketiga, dengan adanya dongeng yang berkarakter anak dapat mengetahui nilai-nilai karakter.